Al-Khibrah Al-Mutsirah's Strategy to Improve Maharah al-Kalam - Damogalad, Rafika; A. Hasan, Adtman (ELOQUENCE : Journal of Foreign Language, 2022)
Background: In the educational process, learning and teaching activities are the most basic activities. This means that whether or not the achievement of educational goals is successful depends on how the teaching and learning process is designed and carried out professionally. The process of learning Arabic requires an educator to use a variety of strategies. Purpose: The purpose of this study was to find out how to increase Maharah al-Kalam using the Al-Khibrah Al-Mutsirah  strategy, and what obstacles and solutions exist in increasing Maharah al-Kalam in students. Method: The method used in this research is Classroom Action Research. Results and Discussion: The results of this study indicate that the Al-Khibrah Al-Mutsirah  Strategy can increase the Maharah al-Kalam for Class X MA Aliyah Luqman Al-Hakim students. This is evidenced by the acquisition of the value of completeness in cycle 1 reaching 36%. Furthermore, in Cycle 2 it reaches 70% so the number of completeness reaches cycle 2 reaches 90%. Conclusions and Implications: The Khibrah Mutsirah strategy could improve students' Maharah al-Kalam abilities. This is based on the results of the Post-test in Cycle 2 that there is an increase in Kalam in Arabic. Where the number of students who have special value categories, namely 2 students (14.28 %) ranges in the value of 90-100, there are 9 students (64.28%) in the good grade category or ranges from 75-89 grades, and 3 students (21.42%) have sufficient category or range from 60-74. While students have low-value categories, and very low scores are no longer available (0%). The implications for Arabic language learning from the results of this study are the importance of selecting and implementing the appropriate learning strategies, especially in improving students' speaking skills, as well as the need for further studies to enrich the references in the field of Arabic language learning.